Microstructure and Mechanical Properties of a New TWIP Steel under Different Heat Treatments - Zhang, Jiaruiming; Bai, Yu; Fan, Wenxue; Zhang, Guanghe; Zhang, Wenhui; Yang, Yang; Hao, Hai (Materials, 2024)
The effects of solution treatment and annealing temperature on the microstructure and mechanical properties of a new TWIP steel that was alloyed from aluminum (Al), silicon (Si), vanadium (V), and molybdenum (Mo) elements were investigated by a variety of techniques such as microstructural characterization and room tensile testing. The austenite grain size grew slowly with the increase in annealing temperature. The relatively weak effect of the solution treatment and annealing temperature on the austenite grain size was attributed to the precipitation of MC and M2C, which hindered the growth of the austenite grain. The plasticity of the TWIP steel in cold rolling and annealing after solution treatment was obviously higher than that in cold rolling and annealing without solution treatment. This was because the large-size precipitates redissolved in the matrix after solution treatment, which were not retained in the subsequently annealed structure. Through cold rolling and annealing at 800 °C after solution treatment, the prepared steel exhibited excellent strength and plasticity simultaneously, with a yield strength of 877 MPa, a tensile strength of 1457 MPa, and an elongation of 46.1%. The strength improvement of the designed TWIP steel was mainly attributed to the grain refinement and precipitation strengthening.